Deformation and Solidification Characteristics and Microstructure of Arc Sprayed Ni-Al Composition Coatings - Wang,Jixiao (2019)
Droplets deformation and solidification characteristics in twin-wire arc sprayed Ni-Al were explored in depth. Both theoretical method and numerical model were established for calculating the deformation process of the droplets impacting on the substrate and their solidification behavior in airflow, which based on two models of the volume of fluid (VOF) dual-phase flow and the standard k-ε. The morphology and the microstructure of the composite coatings were analyzed by XRD, SEM and TEM. The results of the experiment indicate the droplets cooling rate ranges from 3.0×107 to 7.5×107 K/s. The main components of Ni-5wt.% Al coating were Ni solid solution, and a small number of Ni3Al4, Al2O3 and NiO. The main phases of Ni-20wt.% Al coating are Ni3Al and NiAl. EDS and TEM analysis shows that there are a few amorphous and equiaxed crystals in the Ni-Al coating. The surface roughness increases with the decrease of spraying pressure and spraying distance.